Survey of T. annulata and T. buffeli/orientalis in cattle in the region of Erzincan using reverse line blotting - Altay, Kürşat; Aktaş, Münir; Dumanli, Nazir (My University, 2007)
This study was carried out to investigate Theileria annulata and T. buffeli/orientalis in cattle in the region of Erzincan using reverse line blotting (RLB) and microscopical examination. A total of 123 blood samples and thin blood smears were collected from cattle in distinct locations. Thin blood smears were microscopically examined for Theileria piroplasms. The 18S SSU rRNA gene in the DNA of Theileria spp extracted from blood was amplified and used in RLB. For this purpose, PCR products were hybridized with specific probes for over-all Theileria spp., T. annulata and T. buffeli/orientalis as well as Babesia spp. While Theileria spp. were observed in 14 out of 123 cattle, (11.38 %) during microscopical examination, T. annulata was detected in 19 (15.45%) cattle and T. buffeli/orientalis, in 12 (9.76%) by RLB, respectively. Mixed infection was also detected in three samples.
Erzincan yöresinde si?irlarda Theileria annulata ve Theileria buffeli/orientalis'in reverse line blotting yöntemi ile araştirilmasi.
Keywords: Animals; Cattle; DNA, Protozoan; Polymerase Chain Reaction; RNA, Ribosomal, 18S; Theileria; Theileria annulata; Theileriasis; Turkey; protozoal DNA; RNA 18S; animal; animal disease; animal parasitosis; article; blood; cattle; classification; genetics; isolation and purification; parasitology; polymerase chain reaction; Theileria; Theileria annulata; Turkey (republic)